Advantages, Disadvantages, And Policy Needs In The Circular Economy Transition: Evidence From Turkish Manufacturing Industry - KUVVETLİ, Hilal (International Journal of Contemporary Economics and Administrative Sciences, 2025)
The circular economy is an economic sustainability model that aims to increase resource efficiency, minimize waste production, and extend the life cycle of products and materials. It is considered an opportunity for a radical social transformation that will decouple economic growth from virgin resource extraction and use, and carbon/resource-intensive industrial growth. This approach has the potential to provide both environmental, economic, and competitive advantages, especially in the manufacturing industry, which is highly dependent on resources. For this reason, the transition to the circular economy model has an important place in the macroeconomic and industrial policy agendas of various countries, especially the European Union (EU). Policy documents such as the EU's European Green Deal (EGD) and the Circular Economy Action Plan present many innovative policies and regulations within this framework. Circular economy has also gained more importance in Turkey's industrial policies, with the influence of strategies such as the EGD. Turkey makes approximately 50 percent of its exports to the European market. In this context, Turkey's large-scale exporting manufacturing industry companies are taking actions towards the circular economy. The aim of this study is to reveal the perceptions and predictions of large-scale Turkish manufacturing industry companies regarding the circular economy transition, their evaluations about the advantages provided by circular economy actions and their policy expectations towards the circular economy. Within the framework of the exploratory and descriptive structure of this study, qualitative research employed, and in-depth interviews were conducted with managers of 11 large-scale exporting manufacturing industry companies from 9 different manufacturing sectors who have knowledge and experience in the subject. Open and closed-ended questions were asked to the respondents regarding the research questions. In order to formulate the research questions, circular economy literature, which consists of theoretical and applied academic studies, policy documents of various countries and studies of international organizations were used. In the study, where all stages of the content analysis protocol were meticulously applied, the quantification of verbal data and graphical analysis were included. According to the findings of the study, where important and literature-compatible macroeconomic policy inferences were obtained, companies evaluate that the circular economy model is very important in terms of sustainable development and that the possibility of development is very high, arguing “the linear economy has no way to go”. Among the advantages that the circular economy model provides/will provide to companies, economic and financial factors and compliance with regulations stand out. The most necessary policy actions were to establish a clear and strong regulatory framework based on data obtained from the field and to increase the demand for circular products and production by increasing the public interest and awareness towards circularity. The circular economy model is seen important in terms of international activities and reputation rather than its environmental and social advantages and is considered a strategic priority in terms of international competitiveness.